Effect of External load and Salt Concentration on the Performance of Microbial Desalination Cell - Al Balushi, Amal; Al Maqbali, Fatema; Al Saidi, Haitham; Al Maaini, Ibtisam; Mesfin, Anteneh Yeneneh; Sharifzadeh, Bahareh; Al Ajmi, Muna; Jafary, Tahereh (International Journal of Integrated Engineering, 2022)
Microbial desalination cell (MDC) is one of the cost and energy-effective methods that can help people in countries with low income and the people in rural areas without energy infrastructure, get access to desalinated water while treating their wastewater. Despite the advantages of the technology, less is known about the behavior of the internal resistance in MDCs. Therefore, this study mainly focused on the behavior of MDC from the internal and external resistance points of view. The desalination rate of saltwater at different applied external resistance was studied. Moreover, the polarization capacity of the established MDC was investigated. The internal resistance of MDC at different salt concentrations of the desalination chamber was also analyzed and discussed. The findings of the study showed that decreasing the external resistance could increase the current generation of the MDC as the main driving force of desalination. Moreover, it was found that salt concentration in the middle chamber plays a significant role in the internal resistance of MDC and hence on the desalination rate. The lower desalination rate at the lower salt concentration of the desalination chamber could be explained by the high internal resistance of the system. Therefore, integrating MDC with other suitable techniques, e.g., reverse osmosis (RO), for desalination of lower salt concentrations could overcome this challenge. MDC as a standalone desalination system at the current stage of technology might not be practical due to the low current performance of the system. However, it is worth considering it as a green and low-cost technology for the pretreatment stage of the other conventional desalination systems like RO with energy and cost savings while treating the wastewater.